PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA VIII KELAS SD NEGERI 060934 MEDAN - Yuni Rayanti Sinaga; Reflina Sinaga; Sumarlin Mangandar Marianus; Darinda Sofia Tanjung (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article reports students’ learning outcomes applying the role-playing learning model in the theme of the place where I live at class IV of SDN 060934 Medan Johor in the academic year 2021/2022. The research subjects involved the whole fourth-grade students, which consists of 11 male and 11 female students. Data collection techniques used are observation and tests. The results indicate that there is a significant result of students’ learning outcomes on the theme of the Place Where I Live. It is proven from the pretest result that there are four students who completed (18.18%) while 18 students (81.82%) did not complete with an average of 53. In the post-test cycle I there was an increase with 8 students (36.36%) who completed and 14 students who did not complete (63.64%) who did not complete with an average score of 66.3. In the post-test of cycle II, students’ learning outcomes increased to 81.82% from a number of 18 students who completed and 18.18% of four students who did not complete with an average of 84.4. Furthermore, the results of teacher observation in cycle I obtained an average value of 48% and 62% of students’ observations. In Cycle II, the results of teacher observations increased to 82% and 88% of students’ observations. Thus, applying the role-playing learning model can improve students’ learning outcomes on the theme of the place where I live at class IV of SDN 060934 Medan Johor.